Analisis Hukum Perlindungan Konsumen Terhadap Hak-Hak Konsumen Dalam Transaksi Elektronik Di Indonesia - I Made Sudirga (Faculty of Law, Mahasaraswati University, Denpasar, 2025)
This research aims to guarantee the importance of protecting consumer rights as part of efforts to create a just and prosperous society, so an in-depth study is needed. The research method used in this research is a normative juridical method with a statutory approach and a conceptual approach. The legal materials used are Law Number 8 of 1999 as primary legal materials, journal articles and other documents as secondary legal materials and the tertiary legal materials used are legal dictionaries and encyclopedias. Data collection in this research was carried out through literature study (library research). The collected data will be analyzed qualitatively using descriptive-analytical and prescriptive methods. The results of this research state that legal regulations regarding the protection of consumer rights in Indonesia have a strong foundation with the existence of the UUPK and various sectoral regulations. However, its implementation still faces various challenges. Challenges of protecting consumer rights in electronic transactions and e-commerce in Indonesia is multidimensional and requires collaboration between government, business actors, platform e-commerce, consumer protection agencies, and the public.